Effect of The Volume of Banana Fiber As A Polymer Composite Amplifier With Polyester Resin Matrix On The Sound Absorption of Acoustic Materials - rizka fauziah; - Ramli; Yenni Darvina; - Ratnawulan (PILLAR OF PHYSICS, 2022)
Research has been carried out on the banana fiber effect as a polymer composite amplifier with polyester resin matrix on the sound absorption of acoustic materials. Sound Absorber material is made with a variation in the volume of banana fiber that is different from polyester resin. The volume of banana fiber  and polyester resin used  is  15% Fiber:    85%  Polyester Resin,  20%  Fiber:  80%  Polyester Resin, 25% Fiber: 25%  Fiber:    75%   Resin Polyester, 30%  Fiber:    70%  Polyester Resin, 35%  Fiber:    65%  Polyester Resin. So when made composite then the amount of banana fiber used and polyester resin is 100%. Research methods are carried out in the collection of banana fiber, composite manufacturing and testing of sound absorption properties using impedance tubes. The testing of coefficient sound reflection and also sound absorbance coefficient testing is done using sound level meter and signal generator by reference to principle the method of tube impedance via approach to the acoustic box. The banana fiber composite result and polyester resin are able to reflect the sound of highest which is 0.44 in a frequency 500 Hz with fiber 15%. While lowest sound reflection coefficient is 0.06 at a frequency of 8000 Hz and fiber 35%. While in the test the highest value absorbance coefficient that absorbs sound  is  =  0.94 at fiber volume  35%,  and frequency 8000 Hz, while the lowest sound coefficient is 0.56 in fiber 15% and frequency 500 HZ